2001
DOI: 10.1080/09593330.2001.9619163
|View full text |Cite
|
Sign up to set email alerts
|

Development of Artificial Seed Crystal for Crystallization of Calcium Phosphate

Abstract: An artifical seed crystal material consisting of calcium silicate hydrate (5CaO x 6SiO2 x 5H2O : tobermorite crystals) applicable for phosphorus removal by crystallization was developed. Card-house shaped tobermorite crystals were developed on the seed material where orthophosphate crystallized as a calcium phosphate. The seed material can be manufactured by mixing siliceous and calcareous raw materials, pelletizing and subsequent autoclaving. Laboratory experiments were conducted to apply the new developed se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…The factors that affect the phosphorus recovery ratio include chemical factors, such as reaction pH, added magnesium/phosphate-phosphorus (Mg/PO 4 -P) ratio, ammonium-nitrogen/phosphate-phosphorus (NH 4 -N/PO 4 -P) ratio, supersaturation degree, and phosphorus volumetric loading, and physical factors relating to the crystal properties, such as crystal particle size, crystal surface areas, and fluidized conditions (Doyle and Parssons, 2002;Durrant et al, 1999;Hirasawa et al, 2002;Moriyama et al, 2001;Ohlinger et al, 1998;Stratful et al, 2004). Moreover, at some concentrations of suspended solids in the raw water, fine MAP particles are entrained by the suspended solids and flow out with the treated water, causing the recovery ratio to be decreased, in some cases.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The factors that affect the phosphorus recovery ratio include chemical factors, such as reaction pH, added magnesium/phosphate-phosphorus (Mg/PO 4 -P) ratio, ammonium-nitrogen/phosphate-phosphorus (NH 4 -N/PO 4 -P) ratio, supersaturation degree, and phosphorus volumetric loading, and physical factors relating to the crystal properties, such as crystal particle size, crystal surface areas, and fluidized conditions (Doyle and Parssons, 2002;Durrant et al, 1999;Hirasawa et al, 2002;Moriyama et al, 2001;Ohlinger et al, 1998;Stratful et al, 2004). Moreover, at some concentrations of suspended solids in the raw water, fine MAP particles are entrained by the suspended solids and flow out with the treated water, causing the recovery ratio to be decreased, in some cases.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…These results suggest that the colour and phosphorous-removal performance of CSH-lime is considerably higher than that of ALC. Moriyama et al [18] demonstrated that crystal material consisting of calcium silicate hydrate can be used to remove phosphorus through crystallization, and the hydroxyapatite that is produced can be used as a fertilizer. CSH-lime may also be used as a fertilizer if the precipitated CSH-lime can be recovered.…”
Section: Difference In Characteristics and Performance Of Csh-lime Anmentioning
confidence: 99%
“…Physico-chemical treatments and biological nutrient removal are the most commonly used methods for the removal of phosphate from municipal and industrial wastewater (Jenkins and Hermanowich 1991;Stensel 1991;Zhao and Sengupta 1998). Although often used, they hold several disadvantages such as excess sludge production, high chemical demand, and most importantly it is difficult to achieve regulatory guidelines since only 75% to 85% of the phosphate is removed (Moriyama et al 2001).…”
Section: Introductionmentioning
confidence: 99%